The Pattern of School Cooperation with Parents and the Community in Building Student Character at Madrasah Aliyah - Yuliani; Hidayatulloh (Universitas Muhammadiyah Sidoarjo, 2022)
There are three kinds of education, namely education in the family (informal), education in schools (formal), and education in the community (non-formal). Education in the family is the first education for a child and as a child's foundation. The second education includes schools which in the process are systematic and transfer of knowledge. Third, education in the community. The pattern of cooperation between the three is very necessary for the realization of character education. The aims of this study are (1) to analyze the pattern of school cooperation with parents and the surrounding community in shaping the character of students at Madrasah Aliyah Al-Islamy Sedati Mojokerto. (2) Analyzing the factors that support and hinder the pattern of school cooperation with parents and the surrounding community in shaping the character of students at Madrasah Aliyah Al-Islamy Sedati Mojokerto.